Unveiling Islamophobia: navigating its presence in Sweden - Adrián Groglopo; Fereshteh Ahmadi; Jimmy Stephen Munobwa (Cogent Social Sciences)
Political and media narratives often manufacture immigration as a social problem, framing the construction of meaning through the discourses of cultural differences as social, political and security problems. Of specific concern is how Muslims and immigrants from predominantly Muslim countries are perceived as the undesirable ‘Other’. The existence of latent - and many times open - anti-Muslim racism raises concerns about the depth of Sweden’s commitment to inclusivity and non-discrimination. Based on the findings of the Diversity Barometer study, among other sources, this article elucidates the longstanding Islamophobia in Sweden. The Diversity Barometer study is a longitudinal survey tracking attitudes towards ethnic diversity in Sweden since 2005. Our analysis shows how islamophobia manifests in the context of structural racism through attitudes towards people with a Muslim background in Sweden. Political debate and national institutions further entrench the negative narrative. By exploring the structural perspective to islamophobia and racism, the article encourages introspection within Swedish society, challenging preconceived notions that hinder social equality, rights, integration, and social cohesion.